Necrotizing Fasciitis Following Dermal Filler and Thread Lift Procedure: A Case Report with Multidisciplinary and Regenerative Reconstruction Approach - Putri Nurdiyanti; Bayu Fasi Bermani; Betha Egih Riestiano; Eva Yolanda (International Journal of Social Service and Research, 2026)
The rapid pace of modernization and globalization has placed regional languages in a vulnerable position, at risk of being marginalized. This research aims to analyze the existence of regional languages amid the dominance of the national language and foreign languages, as well as to identify the factors causing a decline in the frequency of regional language use in everyday communication. Using a descriptive qualitative research method with a literature review and sociolinguistic observation approach, this study found that language shift occurs significantly, particularly in urban areas. The main factors influencing this phenomenon include the perception of prestige associated with foreign languages, population migration (urbanization), and the lack of language transmission from parents to children. The research results indicate that although regional languages are still regarded as a cultural identity, their active use continues to decline among Generation Z and Generation Alpha. In conclusion, revitalization is necessary through the integration of digital technology, the strengthening of local content in school curricula, and collective awareness within families as the smallest unit of language preservation. These efforts are crucial to ensure that regional languages do not merely become historical artifacts but remain living languages in the modern era.